THE MAKING OF DIGITAL STORYTELLING AS A TOOL FOR PROMOTING THE LEARNING PROCESS IN THE CLASSROOM - Pelayo, Monica Garcia (European Scientific Journal, ESJ, 2013)
This paper is the product of the reflexive work carried out during my academic interaction with college students, where I have incorporated the Information and Communication Technologies (ICT) as a way to foster students’ expression and creativity. This is part of a research project that works on the mode of action research and which aims at exploring and understanding college students’ inner life through digital storytelling, as a means to construct meaning inside the classroom.